Sex-specific weight loss mediates sexual size dimorphism in Drosophila melanogaster. - Nicholas D Testa; Shampa M Ghosh; Alexander W Shingleton (PLoS ONE, 2013)
The selective pressures leading to the evolution of Sexual Size Dimorphism (SSD) have been well studied in many organisms, yet, the underlying developmental mechanisms are poorly understood. By generating a complete growth profile by sex in Drosophila melanogaster, we describe the sex-specific pattern of growth responsible for SSD. Growth rate and critical size for pupariation significantly contributed to adult SSD, whereas duration of growth did not. Surprisingly, SSD at peak larval mass was twice that of the uneclosed adult SSD with weight loss between peak larval mass and pupariation playing an important role in generating the final SSD. Our finding that weight loss is an important regulator of SSD adds additional complexity to our understanding of how body size is regulated in different sexes. Collectively, these data allow for the elucidation of the molecular-genetic mechanisms that generate SSD, an important component of understanding how SSD evolves.